Minerals of Pohorje marbles - Jeršek, Miha (Geologija, 2013)
In the Pohorje Mts, mostly outcrops of calcite marble can be found, which in places turn into dolomite marbles. The protolith carbonate rocks contained also detritical minerals, which remained unchanged or formed new minerals during metamorphosis. Minerals in the Pohorje marbles that can be seen as crystals with the naked eye or 10x mag - nifying loupe and with binocular microscope were investigated. With the aid of Raman microspectroscopy, SEM-EDSanalysis and on the basis of morphological characteristics, the presence of 17 different minerals or group of minerals was confirmed. The mostnumerous and also the most significant were, apart from calcite, tremolite, diopside, grossu - lar and epidote. For the first time, vesuvianiteand scapolite were described in the Pohorje Mts. Particularly rich,as far as crystal faces are concerned, were the crystals of quartz that contained needle-like amphiboles. Other minerals that well supplemented the mineral paragenesis were different minerals of mica and chlorite group, feldspars, magnetite, titanite, pyrite and graphite. The determined mineral association revealed the mineral diversity of Pohorje marbles, offering us a new challenge for the investigation of the characteristics and conditions during the origin of this noble rock, which was highly esteemed already by theRomans, while today it is regaining its value and recognisability.
Keywords: marble; marmor; metamorfne kamnine; mineral; minerali; Pohorje